The story of grain self‐sufficiency: China's food security and food for thought. (18th November 2021) - Niu, Yingnan; Xie, Gaodi; Xiao, Yu; Liu, Jingya; Zou, Huixia; Qin, Keyu; Wang, Yangyang; Huang, Mengdong
Abstract: Grain self‐sufficiency (GSS) is gaining increased attention throughout the world, and this holds particularly true for China. This study, therefore, investigated spatial and temporal patterns of GSS at the county level in China from 1980s to the 2010s; then explored future GSS changes in the 2035s according to China's 2016 dietary nutrition guidelines, under the circumstances of maximum, average and minimum grain yield increase rate; and finally discussed the ability of a county to purchase grain to meet its demands. The results indicate that the number of counties with self‐insufficiency for total grain and ration decreased, and the amount of counties with high‐level self‐sufficiency for total grain and ration increased. However, the change in the number of counties with feed grain self‐insufficiency and high‐level self‐sufficiency is opposite to that of ration and total grain. Eastern China was characterised by high GSS of total grain, ration and feed grain. As for different kinds of grain, high level of GSS distributed in main grain producing areas, such as rice in south China, wheat in western China and Huang Huai Hai Plain, maize in north and northwest China and soybean in northeast China. Qinghai‐Tibet plateau has undergone poor food security in the last 30 years. In the 2035s, China's total GSS level and ration self‐sufficiency level will be improved under the maximum and average grain yield increase rate, whilst for feed grain, the self‐sufficiency level will be improved only under the maximum grain yield increase rate. The Qinghai‐Tibet plateau has always been a fragile area of food security. This study plays the vital function in understanding China's food security and contributes to the optimisation of agricultural production as well as the utilisation of both internal and external markets. Abstract : The grain self‐sufficiency of total grain, ration and feed grain was high in eastern China, but low in western China from 1980s to 2010s. County level grain self‐sufficiency in 2035s will vary at different degrees. The ability of a county to purchase grain from imports to meet its own needs was explored.